The nature of mathematics - Smith, Karl J. ([Place of publication not identified] Brooks/Cole Cengage Learning, 2012)
This book was written for students who needs a mathematics course to satisfy the general university competency requirements in mathematics. Because of the university requirements, many students enrolling in a course that uses my book have postponed taking this course as long as possible .
Chapter1. The nature of problem solving -- Chapter2. The nature of sets -- Chapter3. The nature of logic -- Chapter4. The nature of numeration system -- Chapter5. The nature of numbers -- Chapter6. The nature of algebra -- Chapter7. The nature of geometry -- Chapter8. The nature of networks and graph theory -- Chapter9. The nature of measurements -- Chapter10. The nature of growth -- Chapter11. The nature of financial management -- Chapter12. The nature of counting -- Chapter12. The nature of probability -- Chapter14. The nature of statistics -- Chapter15. The nature of graphs and functions -- Chapter16. The nature of mathematical systems -- Chapter17. The nature of voting and appointment -- Chapter18. The nature of calculus .
Includes index.
Keywords: MATHEMATICS